The Effectiveness of Using Indonesian Language Learning Modules in the Independent Curriculum to Improve Learning Outcomes - Tarigan, Monica Marcelina Br; Hutahaean, Berman; Gultom, Candra Ronitua (Raja Zulkarnain Education Foundation, 2025)
This study aims to explore the effectiveness of using Indonesian language learning modules in the Independent Curriculum (Curriculum Merdeka) to improve student learning outcomes. This research took place at SMP Primbana Medan, in the 2024/2025 academic year. This study used a descriptive qualitative approach with a case study design. The respondents were Indonesian language teachers and students in grades VII, VIII, and IX. Participatory observation guidelines were used to collect research data. This participatory observation technique was reinforced by other techniques, namely in-depth interviews and documentation. To ensure data validity, source triangulation and member checking techniques were conducted with the primary respondents. Effectiveness data were analyzed using a thematic approach through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the use of learning modules encouraged active student involvement, improved understanding of the material, and supported independent and contextual learning. Several obstacles were also found, such as students' difficulties in understanding the modules without guidance and the lack of adjustment of module content to students' learning needs. This study provides strategic recommendations to improve the effectiveness of Indonesian language learning modules in the Independent Curriculum, thereby enhancing student learning outcomes.